Retroperitoneal mucinous cystadenoma with neuroendocrine differentiation: a rare case and comprehensive approach to diagnosis and management - Yen Ho; Wei-Yu Chen; Chung-Howe Lai; Syuan-Hao Syu (Diagnostic Pathology)
Abstract Background Retroperitoneal mucinous cystadenomas are exceptionally rare neoplasms, with limited cases reported in the literature. The occurrence of neuroendocrine differentiation in such tumors is even more uncommon, posing unique diagnostic and management challenges. Case presentation We report a case of a 32-year-old woman who was incidentally diagnosed with a right retroperitoneal cyst during routine prenatal ultrasonography. The patient remained asymptomatic until postpartum, prompting further evaluation of the cyst. Imaging studies identified a large cystic mass, ultimately leading to diagnostic laparoscopy and surgical excision. Histopathological analysis confirmed the diagnosis of a mucinous cystadenoma with neuroendocrine cell proliferation. Discussion This case highlights the complexity of diagnosing and managing retroperitoneal mucinous cystadenomas, particularly those with neuroendocrine features. Given the rarity of these tumors, thorough histopathological examination is crucial to differentiate them from other cystic lesions. Surgical excision remains the definitive treatment, with long-term follow-up essential to ensure complete resolution and monitor for recurrence or malignant transformation. Conclusion Retroperitoneal mucinous cystadenomas with neuroendocrine differentiation represent a rare clinical entity requiring careful evaluation. This report underscores the importance of considering neuroendocrine differentiation in retroperitoneal cystic lesions and emphasizes the role of complete surgical excision followed by close monitoring to ensure favorable outcomes.